SURVIVAL STRATEGIES OF THE JAVANESE LANGUAGE IN NEW CALEDONIA - Subiyantoro . (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
The Javanese language, one of non territorial languages used by minority Javanese migrants in New Caledonia, today is categorized as an endangered language. French domination and lack of language transmission have marginalized this language. This research aims to describe the situation of Javanese language and to examine the strategies the Javanese speakers perform to maintain their language by using qualitative method. The data, in forms of linguistic units, were collected through interviews with representative informants and through direct communications with Javanese language speakers in Nouméa and Kone New Caledonia in February 2013. The analysis shows that linguistic hybridization becomes one of the characteristics of Javanese language in New Caledonia, while the adaptation, integration, increasing the wealth and prestige are the form of its survival strategies to save their language.